COVID-19 vaccination effectiveness and safety in vulnerable populations: a meta-analysis of 33 observational studies - Li, Hui-Jun; Yang, Qi-Chao; Yao, Yang-Yang; Huang, Cheng-Yang; Yin, Fu-Qiang; Xian-Yu, Chen-Yang; Zhang, Chao; Chen, Shao-Juan (Frontiers in Pharmacology, 2023)
Background: Even 3 years into the COVID-19 pandemic, questions remain about how to safely and effectively vaccinate vulnerable populations. A systematic analysis of the safety and efficacy of the COVID-19 vaccine in at-risk groups has not been conducted to date. Methods: This study involved a comprehensive search of PubMed, EMBASE, and Cochrane Central Controlled Trial Registry data through 12 July 2022. Post-vaccination outcomes included the number of humoral and cellular immune responders in vulnerable and healthy populations, antibody levels in humoral immune responders, and adverse events. Results: A total of 23 articles assessing 32 studies, were included. The levels of IgG (SMD = −1.82, 95% CI [−2.28, −1.35]), IgA (SMD = −0.37, 95% CI [−0.70, −0.03]), IgM (SMD = −0.94, 95% CI [−1.38, −0.51]), neutralizing antibodies (SMD = −1.37, 95% CI [−2.62, −0.11]), and T cells (SMD = −1.98, 95% CI [−3.44, −0.53]) were significantly lower in vulnerable than in healthy populations. The positive detection rates of IgG (OR = 0.05, 95% CI [0.02, 0.14]) and IgA (OR = 0.03, 95% CI [0.01, 0.11]) antibodies and the cellular immune response rates (OR = 0.20, 95% CI [0.09, 0.45]) were also lower in the vulnerable populations. There were no statistically significant differences in fever (OR = 2.53, 95% CI [0.11, 60.86]), chills (OR = 2.03, 95% CI [0.08, 53.85]), myalgia (OR = 10.31, 95% CI [0.56, 191.08]), local pain at the injection site (OR = 17.83, 95% CI [0.32, 989.06]), headache (OR = 53.57, 95% CI [3.21, 892.79]), tenderness (OR = 2.68, 95% CI [0.49, 14.73]), and fatigue (OR = 22.89, 95% CI [0.45, 1164.22]) between the vulnerable and healthy populations. Conclusion: Seroconversion rates after COVID-19 vaccination were generally worse in the vulnerable than healthy populations, but there was no difference in adverse events. Patients with hematological cancers had the lowest IgG antibody levels of all the vulnerable populations, so closer attention to these patients is recommended. Subjects who received the combined vaccine had higher antibody levels than those who received the single vaccine.